Quantitative analysis of tumor-infiltrating lymphocytes in meningiomas of the brain - S. I. Tertishniy; L. L. Golubovitch; W. Е. Voteva (Zaporozhye State Medical University, 2016)
Tumor-infiltrating lymphocytes (TIL) are an important component of the microenvironment in brain tumors and particularly in meningiomas. It is considered that immune cell infiltrates in meningiomas of the brain are composed of different populations of immune cells that perform a wide range of functions. Objective: To investigate the quantitative composition and distribution of CD4, CD8, CD20 tumor-infiltrating lymphocytes (TIL) in the tumor microenvironment of the brain meningiomas. Material and methods. Using immunohistochemistry 60 cases of meningiomas were analyzed. Results. The lowest quantity of CD4+ and CD8+ TIL was established in angiomatous subtypes and the median amount of CD4+ and CD8+ TIL in meningothelial subtypes was the highest, it was equal to 9 (1; 26) and 16 (8; 47) cells respectively. It was found that the number of CD4+ TIL was significantly higher in meningothelial variants than the number of CD4+ TIL in angiomatous (p = 0,035) and fibroblastic cases (p = 0,040). The number of CD8+ TIL in meningothelial subtypes was statistically significantly higher than in angiomatous (p = 0,010) and transitional (p = 0,003). We revealed that in grade I meningiomas number of CD8+ TIL significantly exceeded the number of CD4+ TIL (p = 0,003). The CD8+/CD4+ TIL ratio was 1,66. The median number of CD4+ TIL in anaplastic meningiomas was 9 (3; 20) cells, and CD8+ TIL - 14 (9; 80) cells. Although the number of CD8+ TIL exceeded the number of CD4+ TIL, but the results were not statistically significant (p = 0,164). The CD8+/CD4+ TIL ratio was 2,99. Median quantity of CD20+ TIL was increased in the following row: fibroblastic - 1 (0; 6) cells, transitional - 5,5 (0; 10) cells, meningothelial - 14,5 (0; 39) cells and anaplastic meningiomas - 24 (2,5; 46) cells. Conclusions. In benign meningiomas quantity of CD8+ TIL significantly exceeded the number of CD4+ TIL, that can play an important role in limiting the rate of growth of these tumors. There was no statistically significant difference in the number of CD4+, CD8+ and CD20+ TIL between grade I and grade III meningiomas. Interaction of immune cells in the tumor microenvironment is complex and largely depends on the phenotype of TIL, its establishment will be able to uncover the mechanisms of progression in anaplastic meningiomas.